CULTURAL AND COGNITIVE CHALLENGES IN TRANSLATING ENGLISH IDIOMS INTO UZBEK: A LINGUOCULTURAL PERSPECTIVE - Sagdiyeva Umida (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This study explores the cultural and cognitive challenges involved in translating idiomatic expressions from English into Uzbek within the framework of linguoculturology. The findings reveal that translation difficulties arise due to differences in cultural values, metaphorical systems, and conceptual frameworks (Lakoff & Johnson, 1980; Newmark, 1988).